Peningkatan Kapasitas SDM Pengelola Keuangan pada Badan Usaha Milik Desa - Nugroho, Prayudi; Riyanto, Edy; Haptari, Vissia Dewi (Journal Pemberdayaan Masyarakat Indonesia, 2023)
Village-Owned Enterprises (BUMDESA) were established to manage village assets and other potential village-owned resources, in order to improve the welfare of village communities. BUMDESA's activities are currently growing rapidly, but on the other hand there are problems in recording and reporting BUMDESA's financial transactions according to Financial Accounting Standards (SAK). Studies on several BUMDESA in Mojokerto Regency, East Java Province, show that this problem occurs because of the limited accounting competence of BUMDESA personnel. Efforts to increase the capacity of BUMDESA's human resources (HR) are carried out through several activities such as socialization, visitation, mentoring, consulting, and accounting training as well as the introduction of BUMDESA financial accounting applications. The ultimate goal of this activity is that BUMDESA's human resources are able to understand accounting, and are able to independently apply the accounting process to BUMDESA's financial transactions in order to produce BUMDESA's financial reports in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP).